Digital Product and Process Development Systems IFIP TC 5 International Conference, NEW PROLAMAT 2013, Dresden, Germany, October 10-11, 2013, Proceedings - Kovacs, George L.; Kovacs, George L.; Kochan, Detlef.; Kochan, Detlef. (IFIP Advances in Information and Communication Technology, 2013)
This book constitutes the refereed proceedings of the IFIP TC 5 International Conference on Digital Product and Process Development Systems, NEW PROLAMAT 2013, held in Dresden, Germany, in October 2013. The conference succeeds the International Conference on Programming Languages for Machine Tools, PROLAMAT 2006, held in Shanghai, China in 2006. In order to demonstrate the new orientation toward IT innovations, the acronym PROLAMAT has been changed into NEW PROLAMAT and is now interpreted as Project Research on Leading-Edge Applications and Methods for Applied Technology. The 42 revised papers were carefully reviewed and selected for inclusion in the volume. They have been organized in the following topical sections: digital product and process development; additive manufacturing; quality management; standardization and knowledge management developments; and simulation of procedures and processes.